Nilai Dan Fondasi Pembangunan Ekonomi Dalam Islam - Masrizal Masrizal; Sitti Hamidah Mujahidah; Afifah Nur Millatina; Sri Herianingrum (Institut Agama Islam Negeri Madura, 2019)
Economic development in Islam is a balance and sustainable in terms of material or non-material resulting from Islamic morals. The aim is not merely material welfare in the world, but also the welfare of the hereafter. This paper explains the value and basis of economic development. The basis and value of economic development in Islam consists of tauhid, rububiyah, khilafah and tazkiyah. The principle of tauhid representing all human activities in the form of human resources (muámalah) is framed with the support of relations with God. The Rububiyah principle from God is a god who creates nature, devotes, supports, gives sustenance, everything under his knowledge, skill and understanding that is infinite. The principle of khilafah as a human being, which prosper the earth and become the responsible to Allah, and manage the resources, that are mandated to support and tazkiyah to purify humans in assistance with Allah, their fellowmen and the natural environment, society and country.[Pembangunan Ekonomi dalam Islam merupakan keseimbangan dan berkelanjutan antara aspek materi maupun non materi yang dihasilkan dari moral-moral Islam. Tujuannya bukan semata-mata kesejahteraan material di dunia, tetapi juga kesejahteraan akhirat. Paper ini bertujuan untuk menjelaskan nilai dan dasar dalam pembangunan ekonomi. Dasar dan nilai pembangunan ekonomi dalam Islam terdiri dari tauhid, rububiyah, khilafah dan tazkiyah. Prinsip tauhid merupakan segala aktivitas manusia dalam hubungannya dengan alam dan sumber daya manusia (muámalah) dibingkai dengan kerangka hubungan dengan Allah. Prinsip rububiyah bahwa Allah ialah Tuhan yang menciptakan alam, memilikinya, memberi rezeki, alam dan segala isinya di bawah pengetahuan, kehendak dan kebijaksanaan-Nya yang tidak terhingga. Prinsip khilafah bahwa manusia sebagai wakil Allah SWT di muka bumi untuk memakmurkan bumi dan bertanggung jawab kepada Allah SWT tentang pengelolaan alam dan segala sumber daya yang diamanahkan kepadanya. Tazkiyah mensucikan manusia dalam hubungannya dengan Allah SWT, sesamanya dan alam lingkungan, masyarkat dan negara.]